Peptide Targeted Gold Nanoplatform Carrying miR-145 Induces Antitumoral Effects in Ovarian Cancer Cells - Edison Salas-Huenuleo; Andrea Hernández; Lorena Lobos-González; Iva Polakovičová; Francisco Morales-Zavala; Eyleen Araya; Freddy Celis; Carmen Romero; Marcelo J. Kogan (MDPI AG, 2022)
One of the recent attractive therapeutic approaches for cancer treatment is restoring downregulated microRNAs. They play an essential muti-regulatory role in cellular processes such as proliferation, differentiation, survival, apoptosis, cell cycle, angiogenesis, and metastasis, among others. In this study, a gold nanoplatform (GNPF) carrying miR-145, a downregulated microRNA in many cancer types, including epithelial ovarian cancer, was designed and synthesized. For targeting purposes, the GNPF was functionalized with the FSH33 peptide, which provided selectivity for ovarian cancer, and loaded with the miR-145 to obtain the nanosystem GNPF-miR-145. The GNPF-mir-145 was selectively incorporated in A2780 and SKOV3 cells and significantly inhibited cell viability and migration and exhibited proliferative and anchor-independent growth capacities. Moreover, it diminished VEGF release and reduced the spheroid size of ovarian cancer through the damage of cell membranes, thus decreasing cell viability and possibly activating apoptosis. These results provide important advances in developing miR-based therapies using nanoparticles as selective vectors and provide approaches for in vivo evaluation.